Language Attitude Toward English Learning Among Non-English College Students - Mufidah Yusroh (Darussalam English Journal (DEJ), 2024)
This study explored the language attitude toward English learning in IAI Ibrahimy Genteng Banyuwangi. The aim of this study was to find out the attitude of the non-English college students toward English language. There were 46 participants from Islamic primary school (PGMI) in the 7th semester in IAI Ibrahimy Genteng Banyuwangi. In this research, a descriptive quantitative method was used as the field research. The data was taken through closed-ended questionnaire. The participants were asked to fill out a questionnaire about the language used and general language attitudes through the Google Form. The results showed that there are three components of language attitudes namely; 1) language attitudes toward cognitive component showed that there was 90% or 41 out of 46 students reflected positive attitude; 2) language attitudes toward affective component showed that there was 52.6% or 24 out of 46 students reflected positive attitude; 3) language attitudes toward conative component showed that there was 59.8% or 27 out of 46 students reflected positive attitude. These three components of language attitudes were then can be concluded that the dominant attitude reflected by the non-English college students is positive.